Left atrial volume predicts adverse cardiac and cerebrovascular events in patients with hypertrophic cardiomyopathy - Tani, Tomoko (BioMed Central, 2011)
AIMS: To prospectively evaluate the relationship between left atrial volume (LAV) and the risk of clinical events in patients with hypertrophic cardiomyopathy (HCM). METHODS: We enrolled a total of 141 HCM patients with sinus rhythm and normal pump function, and 102 patients (73 men; mean age, 61 ± 13 years) who met inclusion criteria were followed for 30.8 ± 10.0 months. The patients were divided into two groups with or without major adverse cardiac and cerebrovascular events (MACCE), a composite of stroke, sudden death, and congestive heart failure. Detailed clinical and echocardiographic data were obtained. RESULTS: MACCE occurred in 24 patients (18 strokes, 4 congestive heart failure and 2 sudden deaths). Maximum LAV, minimum LAV, and LAV index (LAVI) corrected for body surface area (BSA) were significantly greater in patients with MACCE than those without MACCE (maximum LAV: 64.3 ± 25.0 vs. 51.9 ± 16.0 ml, p = 0.005; minimum LAV: 33.9 ± 15.1 vs. 26.2 ± 10.9 ml, p = 0.008; LAVI: 40.1 ± 15.4 vs. 31.5 ± 8.7 ml/mm(2), p = 0.0009), while there were no differences in the other echocardiographic parameters. LAV/BSA of ≥ 40.4 ml/m(2 )to identify patients with cardiovascular complications with a sensitivity of 73% and a specificity of 88%. CONCLUSION: LAVI may be an effective marker for detecting the risk of MACCE in patients with HCM and normal pump function.